2015
DOI: 10.1186/s13227-015-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

The making of an octopus arm

Abstract: BackgroundMost of our current findings on appendage formation and patterning stem from studies on chordate and ecdysozoan model organisms. However, in order to fully understand the evolution of animal appendages, it is essential to include information on appendage development from lophotrochozoan representatives. Here, we examined the basic dynamics of the Octopus vulgaris arm’s formation and differentiation - as a highly evolved member of the lophotrochozoan super phylum - with a special focus on the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 80 publications
5
51
0
Order By: Relevance
“…Overall, our data indicate that after vena cava injection the radioactive solution efficiently circulates throughout the body, reaches all organs, and is efficiently retained by organs with a higher metabolic rate. 18 F-FDG Uptake in Regenerating Arm 18 F-FDG PET scanning of the 2 animals with a regenerating arm showed that activity in the nonregenerating arms was higher at the central arm axes. This finding could be due to the massive population of neuronal cells that forms the peripheral nervous system of the arm and is located at its center.…”
Section: Biodistribution Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, our data indicate that after vena cava injection the radioactive solution efficiently circulates throughout the body, reaches all organs, and is efficiently retained by organs with a higher metabolic rate. 18 F-FDG Uptake in Regenerating Arm 18 F-FDG PET scanning of the 2 animals with a regenerating arm showed that activity in the nonregenerating arms was higher at the central arm axes. This finding could be due to the massive population of neuronal cells that forms the peripheral nervous system of the arm and is located at its center.…”
Section: Biodistribution Studiesmentioning
confidence: 99%
“…This finding could be due to the massive population of neuronal cells that forms the peripheral nervous system of the arm and is located at its center. Like other neural structures, neurons of the peripheral nervous system consume a large amount of glucose to sustain their function and thus show high 18 F-FDG uptake. Activity in the regenerating arm was measured at 2 locations-the base and the tip-and was compared with activity in the nonregenerating arms of the same animal.…”
Section: Biodistribution Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies focusing on species-specific gene expression (Navet et al, 2008; Nödl et al, 2015) have shown that certain features of cephalopod muscle development seem to be specific to this molluscan class. Therefore, more information will be necessary in order to understand the molecular basis of this highly complex and adapted tissue type.…”
Section: Muscle Morphogenesis In Cephalopodsmentioning
confidence: 99%